Examining the Role of Gender Diversity, Foreign Ownership, and Slack Resources in Driving CSR Disclosure: Evidence from Indonesia's Energy Sector - Shiva Karlina Dewi; Syamsul Hilal; Weny Rosilawati (Golden Ratio of Auditing Research, 2026)
Transparency through Corporate Social Responsibility (CSR) disclosure has become a critical issue in the energy sector, which often faces public scrutiny regarding its environmental and social impacts. However, the internal factors that drive energy companies in Indonesia to enhance their CSR disclosure remain underexplored. This study aims to analyze the influence of gender diversity in management, foreign ownership, and organizational slack resources on the extent of CSR disclosure in energy sector companies. This study employs a quantitative approach using secondary data obtained from annual reports and sustainability reports of energy sector companies listed on the Indonesia Stock Exchange for the period 2021–2024. A total of 16 companies met the sample selection criteria, resulting in 48 observational data points. Data were analyzed using multiple linear regression with SPSS 25.0 software. The results show that all three independent variables have a positive and significant effect on CSR disclosure. Gender diversity has a t-value of 4.454 with a significance of 0.000, foreign ownership has a t-value of 4.737 with a significance of 0.000, and slack resources has a t-value of 8.376 with a significance of 0.000. Simultaneously, these three variables significantly influence CSR disclosure, with an F-value of 82.447 and a significance of 0.000. The coefficient of determination (R²) of 0.849 indicates that 84.9% of the variation in CSR disclosure can be explained by gender diversity, foreign ownership, and slack resources. These findings confirm stakeholder theory, suggesting that pressure from stakeholders and the availability of resources encourage companies to be more transparent and socially responsible. This study provides practical implications for energy sector management to strengthen gender diversity policies at the managerial level and optimize resource allocation to improve the quality of sustainability reporting. Furthermore, the results offer insights for regulators in formulating policies that promote CSR transparency in the energy sector.